EVALUASI KOMPREHENSIF KINERJA RETURN PER UNIT RISK SEKTOR-SEKTOR INDUSTRI JASICA - Fongnawati Budhijono; Sugiarto Sugiarto; Januar Wahjudi; Bayu Laksma Pradana (Jurnal Bina Akuntansi, 2022)
This study analyzes the performance of return per unit risk of industrial sectors that are members of the JASICA index (Jakarta Stock Industrial Classification) index. The sample used is 900 data on average returns per unit risk from each industrial sector for the period 2004 to 2018, which is generated from 35235 daily return data from all sectors of the JASICA Index. Data obtained from the Bloomberg terminal. Data analysis tools used in this study include descriptive statistics, trend analysis, ANOVA and Tukey HSD Post hoc test. From descriptive statistics, it is found that sector JAKTRAD produces the highest average return per unit risk, followed by sector JAKPROP, sector JAKBIND, sector JAKCONS and sector JAKFIN, and so on. In descriptive statistics, sector JAKAGRI is the sector that produces the lowest average return per unit of risk. Further analysis of the trend of the average return per unit risk in the period of observation does not show any significant differences in the direction of movement between the performance of one sector and other sectors. The results of the ANOVA and Tukey HSD Post hoc tests only found that the average return per unit risk of Sector JAKAGRI was significantly different from the average return per unit risk of sector JAKPROP and sector JAKTRAD, while the other sectors did not show a significant difference.